Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
F(x) = 2
F(x) = 3x - 1
2 = 3x - 1
3x = 3, x = 1
Solution: x = 1
F(x) = 3x - 1
2 = 3x - 1
3x = 3, x = 1
Solution: x = 1
Answer:
D. {1}
Explanation:
given f(x) = 3x - 1
for f(x) = 2
3x - 1 = 2
3x = 2 + 1
3x = 3
x = 3/3
x = 1
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.